VARIABILITY NET PRIMERY PRODUCTIVITY IN INDIAN OCEAN THE WESTERN PART OF SUMATRA - Amelia, Nina Miranda; Sari, T. Ersti Yulika; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Remote sensing method was used to analyze the state of the aquatic environment which aims to see the characteristics of the spatial and temporal distribution of concentrations of net primary productivity (NPP) in the western Indian Ocean Sumatra with spatial and temporal analysis. Image data NPP obtained fromsatellite image processing Aqua MODIS Level 4 in 2013. This study uses QGIS 2.18. Net primary productivity (NPP) representatives phytoplankton biomass as the basis for the food chain of aquatic organisms in the ocean. The results of this study showed that the concentration of NPP in the western Indian Ocean Sumatra in 2013 are statistically the highest in February is 739,4 gCm2/day, while the lowest in January is 554,0 gCm2/day. Spatially the concentration of NPP highest tends to be found in the coastal waters because it is influenced by the nutrients, ocean mass, chlorophyll-a and the concentration of NPP the lowest visualization tends to be at off the coast. Need to do further research on concentration NPP insitu.Keywords: Aqua MODIS Level 4, net primary productivity (NPP), the western Indian Ocean Sumatra, spatial and temporal.